Sosialisasi Pkm Manajemen Usaha Coffee Shop Menggunakan Business Model Canvas Berbasis Internet Of Things - Yulianto, Harry; Arni, Sitti; Syamsuri, Helmy (PT. Gudang Pustaka Cendekia, 2025)
The growth of coffee shop businesses in Indonesia faces significant challenges, particularly for small and medium enterprises (SMEs) that often encounter limitations in business management, marketing, and technology adoption. This community engagement initiative aims to assist the